Analysis and impact of a multidisciplinary lymphoma virtual tumor board. Issue 14 (5th December 2020) - Habermann, Thomas M.; Khurana, Arushi; Lentz, Ruth; Schmitz, John J.; von Bormann, Alexander G.; Young, Jason R.; Hunt, Christopher H.; Christofferson, Sara N.; Nowakowski, Grzegorz S.; McCullough, Kristen B.; Horna, Pedro; Wood, Adam J.; et al.
Abstract: The aim is to prospectively evaluate the impact of a multidisciplinary lymphoma virtual tumor board. The utility of multi-site interactive lymphoma-specific tumor boards has not been reported. The Mayo Clinic Lymphoma Tumor Board is a component of the International Mayo Clinic Care Network (MCCN). The format includes the clinical case presentation, presentation of radiology and hematopathology findings by the appropriate subspecialist, proposed treatment options, review of the literature pertinent to the case, pharmacy contributions, and discussion followed by recommendations. Three hundred and nine consecutive highly selected real-time cases with a diagnosis of lymphoma were presented at the Mayo Clinic Lymphoma Tumor Board from January 2014 to June 2018 and decisions were prospectively tracked to assess its impact on the treatment decisions. A total of 309 cases were prospectively evaluated. One hundred and forty (45.3%) cases had some changes made or recommended. The total changes suggested were 179, as some cases had more than one recommendation. There were 93 (30%) clinical management recommendations, 45 (14.6%) additional testing recommendations, 29 (9.4%) pathology changes, and 6 (1.9%) radiology changes. In an electronic evaluation process, 93% of the responders reported an improvement in knowledge and competence, and 100% recommended no change in format of the board. A multidisciplinary lymphoma tumor board approach was found to have a meaningful impact on lymphoma patients while enhancing interdisciplinary interactions and education for multiple levels of the clinical care team.